Problems of rational planning in public organizations: an empirical assessment of the conventional wisdom - Boyne, George A. et al (2004)
Rational planning is widely regarded as difficult because of the technical problems of obtaining and interpreting relevant data and the political problems of rivalry between planners and service deliverers. Provided here is the first empirical test of these traditional hypotheses on the problems of rational planning in public agencies. The context of the empirical analysis is a recent attempt by UK local authorities to introduce a new planning system. The statistical results suggest that the problems of rational planning are largely technical (lack of resources and expertise) rather than political. Potential explanations for these results are identified, and the implications for theories of rational planning are considered. - Reproduced.
Keywords: Organizations; Public administration